(untitled) (Baghdad Science Journal, 2016)
The present work involved synthesis of serval new substituted tetrazole via Schiff bases for trimethoprim drug by two steps. The first step involved direct reaction of different ketones and aldehydes with trimethoprim producing the corresponding Schiff bases (1-10), whereas the second step, involved preparation new tetrazoles derivatives (11-20) through reaction of the ready Schiff bases (in the first step) with sodium azidein in dioxin. The prepared compounds were characterized by UV, FT-IR, and some of them by 13C-NMR, 1H-NMR spectroscopy and physical properties.